Oxidative stress in metabolic syndrome / Profesor Dr. Hapizah Mohd Nawawi … [et al.] - Mohd Nawawi, Hapizah; Tengku Ismail, Tengku Saifudin; S. Krishnapilla, Ambigga devi; Ramli, Anis Safura; T. Osman, Muhammad (Research Management Institute (RMI), 2011)
Background: Metabolic syndrome (MS) is a cluster of abdominal obesity, atherogenic dyslipidaemia, hypertension and insulin resistance with or without hyperglycaemia associated with increased risk of coronary heart diseases. There may be a possible link between MS, central obesity and increased markers of oxidative stress. The oxidative stress in central obesity and MS with different glycaemic status is still unclear. Objective: The aim of our study was to evaluate the oxidative stress in central obesity and MS subjects with different glycaemic status and subjects with central obesity without MS. Design: A total of 260 subjects (Mean±SD : 53±11, 66 Males) were randomly recruited and divided into 5 groups: central obesity without MS (OBXMS), MS with diabetes (MSDM), MS with impaired fasting glucose (MSIFG), MS with normoglycaemia (MSNG) and normal control (NC). In addition, MSDM, MSIFG and MSNG were grouped as all MS group with a total number of 156. The blood levels of oxidized low-density lipoprotein (oxLDL) and 8-Isoprostane were evaluated. Results: OBXMS group was not significantly different compared to NC group. MSDM group compared to NC group had higher 8-Isoprostane (p<0.001).MSIFG group compared to NC group had higher oxLDL (p<0.001) and 8-Isoprostane (p<0.001). MSNG group compared to NC group had higher 8-Isoprostane (p<0.001). All MS group compared to NC group had higher oxLDL (p<0.05) and 8-Isoprostane (p<0.001). All MS group compared to OBXMS group had higher 8-Isoprostane (p<0.001). Conclusions: MS irrespective of glycaemic status has enhanced oxidative stress compared to controls. There is enhanced oxidative stress in central obesity especially in the presence of MS, suggesting high coronary risk of MS subjects.